Dziejowe konteksty oraz tendencje reform szkolnych na ziemiach polskich od XVIII do XX wieku (do 1939 roku) - Jakubiak, Krzysztof; Jamrożek, Wiesław (Wydawnictwo Naukowe UAM, 2014)
The authors of the essay present both historic dimensions and main tendencies of organizational assumptions and curricular educational reforms in Polish territories from the Enlightenment till the Second World War. Research shows that challenges of civilization, changes of the sets of upbringing and attempts to offer democratic access of society to education were factors which stimulated and directed the processing of educational reforms in then Europe, Poland included. The main educational reforms were initiated by processes of social and political changes. The state was the mainspring of educational reforms in Europe of modern times. During the Enlightenment, the state took over schools, which resulted in adopting an act establishing the National Education Commission. In the Duchy of Warsaw, the Educational Association created a framework of educational administration connected with the social factor of school supervision. The development of educational legislation took place in the second half of the 19th century. At that time education in Polish territories was connected with the schooling systems of the invaders. The reforms initiated by Poles were to modernize the Polish nation and strengthen its social, political and economic condition. The educational reforms in Poland after regaining Independence were to help rebuild, modernize and strengthen the reborn state.
Historical Concepts and Tendencies of Educational Reforms in Polish Territories From the 18th till 20th Century (Until 1939)
Keywords: educational reforms; Polish territories from the 18th till 20th century